2023
DOI: 10.1097/aci.0000000000000891
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarettes and asthma in adolescents

Abstract: Purpose of review E-cigarettes have been long purported to be a mechanism of harm reduction in current smokers. However, market expansion to adolescents has been aggressive, despite government interventions. Research examining the adverse effects of e-cigarettes in teens with asthma has been limited. We discuss the most recent data on the pulmonary manifestations of e-cigarettes use and exposure in adolescents with asthma. Recent findingsAdolescents with asthma are more likely to be e-cigarette users than thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
1
4
0
Order By: Relevance
“…The results reflect the potential impact of exposure to e-cigarette marketing on susceptibility to future vaping among Black adolescents. These findings echo recent research regarding the impact of exposure to e-cigarette marketing on susceptibility to future vaping among adolescents [9,27,[32][33][34]. However, the results differed for the Latino adolescent group, where exposure to e-cigarette marketing was not significantly associated with susceptibility to future vaping.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The results reflect the potential impact of exposure to e-cigarette marketing on susceptibility to future vaping among Black adolescents. These findings echo recent research regarding the impact of exposure to e-cigarette marketing on susceptibility to future vaping among adolescents [9,27,[32][33][34]. However, the results differed for the Latino adolescent group, where exposure to e-cigarette marketing was not significantly associated with susceptibility to future vaping.…”
Section: Discussionsupporting
confidence: 79%
“…Regarding health outcomes, in 2019, e-cigarette use, or vaping, was associated with 2807 cases of lung injury and 68 deaths in the US (e-cigarette use, or vaping, -associated lung injury: EVALI) [8]. In addition, the use of e-cigarettes by adolescents has been associated with an increased probability of respiratory symptoms, such as cough and wheezing, and health complications, including exacerbation of asthma and bronchitis symptoms [9][10][11]. E-cigarette use among youth and in animal models has been associated with an increase in pulmonary inflammation [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, many studies reported that E-cigarette users are exposed to large amounts of toxic chemical compounds, including carbonyl, volatile organic compounds, and nicotine, as harmful for both consumers and adjacent individuals. It has been reported that nicotine-containing E-cigarettes strengthen the person's physical dependence on nicotine with adverse effects on brain function of growing adolescents [ 5 , 36 , 37 ]. However, studies have shown that the toxic chemical compounds of E-cigarettes are less than ordinary cigarettes, but there is much debate about the components and toxicity [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since E-cigarettes contain nicotine, they are also dangerous for all age groups. Nicotine is a highly addictive material with various side effects on the brain, pregnant women, and fetuses [ 5 ]. E-cigarette users were already smokers, or they had experience of addiction cessation in the past [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of government measures, market growth of e-cigarettes to adolescents has been robust, and research investigating the negative consequences of e-cigarettes in teens with asthma has been limited. Rao and Afolabi [6] review data on the respiratory manifestations of e-cigarettes exposure and utilization in adolescents with asthma. They describe studies on e-cigarette trends, cytotoxicity of aerosol, and relationships with the diagnosis and symptoms of asthma.…”
mentioning
confidence: 99%